THE ROLE OF SUSTAINABLE DEVELOPMENT IN COUNTRY POLICY - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The 1987 Brundtland Report defined sustainable development as “development which meets the needs of the present without compromising the ability of future generations to meet their own needs (Bartelmus, 2012). At the heart of this concept is the belief that over the long term, social, economic and environmental objectives should be complementary and interdependent in the development process. In 1992, the Rio Summit established sustainable development as the guiding vision for development in both industrialized and developing countries, and for international development co-operation (Chung, 2009).